2021
DOI: 10.1142/s2010135x21400038
|View full text |Cite
|
Sign up to set email alerts
|

Electric, magnetic and microstructural features of the La2CoFeO6 lanthanide ferrocobaltite obtained by the modified Pechini route

Abstract: In the search for new materials with applicable magnetic properties in spintronic devices, the aim of this work is to report the synthesis of the lanthanide ferrocobaltite La2CoFeO6 using the modified Pechini route; the experimental study of structural, morphological and magnetic properties, and the analysis of the electronic structure and bands are obtained in the framework of the Density Functional Theory. Rietveld refinement of experimental X-ray diffraction patterns revealed the crystallization of this oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Haripriya et al have identified LCFO as a long-range antiferromagnet with a Neel temperature of 270 K, which is observed in the rhombohedral phase [3]. In the recent past, LCFO and doped LCFO have been studied extensively by various researchers for diverse applications [4][5][6][7][8][9][10][11]. It was found that multiple spin states of the transition metal ions in perovskites result in manifestation of multiple magnetic phases in perovskites.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Haripriya et al have identified LCFO as a long-range antiferromagnet with a Neel temperature of 270 K, which is observed in the rhombohedral phase [3]. In the recent past, LCFO and doped LCFO have been studied extensively by various researchers for diverse applications [4][5][6][7][8][9][10][11]. It was found that multiple spin states of the transition metal ions in perovskites result in manifestation of multiple magnetic phases in perovskites.…”
mentioning
confidence: 99%
“…The crystalline structure of LCFO has been observed in rhombohedral, orthorhombic, monoclinic, or a combination of these phases, as reported by different researchers depending on differences in synthesis routes and experimental parameters [8][9][10]. The crystal symmetry of perovskites is known to have a profound effect on their magnetic properties.…”
mentioning
confidence: 99%
See 2 more Smart Citations